Antonio Favaro e i suoi corrispondenti - Michele Camerota (Galilæana)
The Museo Galileo has recently published online the vast collection of Antonio Favaro’s manuscripts, documents, and letters (Thek@ Favaro: https://teche.museogalileo.it/favaro/it/). The value of this material for the reconstruction of Favaro’s crucial work –especially in the field of Galilean studies– is absolutely essential. This brief contribution, based on a talk given on September 10, 2021, at the Museo Galileo, outlines the editorial criteria adopted by the Edizione Nazionale of Galileo’s works, which Favaro carried out between 1890 and 1909. The paper also highlights the significance of Favaro’ s extraordinary correspondence (over ten thousand letters) for a deeper understanding of the connections and collaborations among European historians of science from the late 19th to the early 20th century.